Leiomyosarcoma of the Mesenteric Root: A Strategic Location of a Rare Tumor - Yoram Kluger; Offir Ben-Ishay (Case Reports in Oncology, 2015)
High mesenteric root sarcomas are difficult to manage due to their proximity to the superior mesenteric vessels. Resection of these tumors along with the blood vessels may lead to a complicated and protracted convalescence for the patient. Resection remains the main treatment modality for these tumors. During operation on high mesenteric root sarcomas, sound clinical judgment is needed for the decision not to sacrifice vital blood vessels.